Enhancing Collaboration Between Transportation Education And Industry In Indonesia: A Cadet Perspective - Jaya Alamsyah; Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This qualitative study investigates the perspectives of 50 cadets enrolled in Indonesian transportation institutes on collaboration between transportation education and industry. The research reveals a high perceived importance of industry-academia collaboration, highlighting its value in providing real-world experience and industry insights. However, challenges such as curriculum misalignment, limited practical training opportunities, and ineffective industry feedback mechanisms hinder effective collaboration. Recommendations include strengthening collaboration through internships and industry projects, regularly reviewing and updating curricula, expanding practical training opportunities, establishing structured industry feedback mechanisms, providing professional development for educators, and promoting lifelong learning. Implementing these recommendations can enhance collaboration, improve education programme relevance, and better prepare students for the transportation sector's demands. This research contributes to the development of a skilled workforce, driving the growth and competitiveness of the transportation industry in Indonesia.